Proper doses of brassinolide enhance somatic embryogenesis in different competent Korean pine cell lines during embryogenic callus differentiation - Nie, Shuai; Yan, Yong; Wang, Yue; Liu, Shanshan; Guo, Wenhui; Yang, Ling; Shen, Hailong (Frontiers in Plant Science, 2024)
Somatic embryogenesis has proven to be the most effective technology for the large-scale propagation and accelerated breeding of conifers. Somatic embryogenesis of the ecologically and economically important Korean pine has been successfully carried out. However, the embryogenic competence of callus gradually decreases as the subculture cycle progresses, which greatly hinders the development of commercial micropropagation of improved Korean pine material. To address this problem, we studied three types of embryogenic calli with different somatic embryogenic competence and cultured them with different concentrations of brassinolides during the proliferation stage. Our study revealed that calli with different embryogenic strengths responded differently to different concentrations of brassinolide , but the effect after the addition of brassinolide was very uniform. The addition of brassinolides during the proliferation phase of embryogenic callus may help to stimulate the biological activity of callus during the proliferation process and improve the level of cell metabolism, which is accompanied by a reduction in storage substances. Brassinolides could reduce the level of endogenous auxin IAA in embryogenic callus and increase the level of abscisic acid to regulate cell division and differentiation. In addition, the MDA content in the callus was significantly decreased and the activity of antioxidant enzymes was significantly increased after the addition of brassinolides. During the proliferation of embryogenic callus, brassinolides are added to participate in the metabolism of phenylpropane in the cells and to increase the activity of phenylalanine ammonia-lyase and the content of lignin in the cells. Our results shed light on the mechanism of brassinolides in Korean pine somatic embryogenesis. They provide a scientific basis for improving the embryogenesis of Korean pine embryogenic cells and offering a reference for the optimizing somatic embryogenesis in other conifer species.